Recurrent Malignant Melanoma Detected on 18F-Fluciclovine PET/CT Imaging for Prostate Cancer. (October 2017) - Teoh, Eugene J.; Tsakok, Maria T.; Bradley, Kevin M.; Hyde, Katherine; Subesinghe, Manil; Gleeson, Fergus V.
Abstract : Abstract: A 66-year-old man presented with biochemical recurrence of prostate cancer and underwent 18 F-fluciclovine PET/CT to detect sites of recurrence. He had a history of resected truncal stage IIIC malignant melanoma, with bilateral axillary node involvement on sentinel node biopsy, in complete remission for 3 years. 18 F-fluciclovine PET/CT demonstrated an incidental fluciclovine-avid right axillary node (SUVmax = 4.3). Diagnostic sampling confirmed recurrent malignant melanoma.